Text-book of forensic medicine and toxicology - Buchanan, R. J. M. (Robert James McLean), 1864-1925 (Salt Lake City, UT : Project Gutenberg, 2024)
"Text-book of Forensic Medicine and Toxicology" by R. J. M. Buchanan is a scientific publication written in the early 20th century. This textbook serves as a comprehensive guide on the application of medical knowledge to legal contexts, focusing on various aspects of forensic medicine and toxicology. It is likely aimed at medical students and practitioners who need to understand the intersection between healthcare and legal issues. The opening of the text introduces the domain of forensic medicine, defining it as the application of medical knowledge to legal questions concerning health, illness, and death. It emphasizes the critical role of medical practitioners in legal contexts, underscoring the responsibility they have when called upon to provide expert testimony in cases of suspicious or unnatural deaths. Furthermore, it outlines the historical significance of the field and discusses the necessity for medical professionals to equip themselves with knowledge in forensic practices to aid in the administration of justice. (This is an automatically generated summary.)
Release date is 2024-11-27
Richard Tonsing and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Medical jurisprudence; Poisons